A Recombinant Human Pluripotent Stem Cell Line Stably Expressing Halide-Sensitive YFP-I152L for GABAAR and GlyR-Targeted High-Throughput Drug Screening and Toxicity Testing - Kuenzel, Katharina; Friedrich, Oliver; Gilbert, Daniel F. (Frontiers in Molecular Neuroscience, 2016)
GABAARs and GlyRs are considered attractive drug targets for therapeutic intervention and are also increasingly recognized in the context of in vitro neurotoxicity (NT) and developmental neurotoxicity (DNT) testing. However, systematic human-specific GABAAR and GlyR-targeted drug screening and toxicity testing is hampered due to lack of appropriate in vitro models that express native GABAARs and GlyRs. We have established a human pluripotent stem cell line (NT2) stably expressing YFP-I152L, a halide-sensitive variant of yellow fluorescent protein (YFP), allowing for fluorescence-based functional analysis of chloride channels. Upon stimulation with retinoic acid, NT2 cells undergo neuronal differentiation and allow pharmacological and toxicological evaluation of native GABAARs and GlyRs at different stages of brain maturation. We applied the cell line in concentration-response experiments with the neurotransmitters GABA and glycine as well as with the drugs strychnine, picrotoxin, fipronil, lindane, bicuculline and zinc and demonstrate that the established in vitro model is applicable to GABAAR and GlyR-targeted pharmacological and toxicological profiling. We quantified the proportion of GABAAR and GlyR-sensitive cells, respectively, and identified percentages of approx. 20% each within the overall populations, rendering the cells a suitable model for systematic in vitro GABAAR and GlyR-targeted screening in the context of drug development and NT/DNT testing.